Elementary Analysis of Segmental Stator Flux Switching Permanent Magnet Machine - S. M. N. S. Othman; M. F. Omar; S. K. Rahimi; E. Sulaiman (Institute of Advanced Engineering and Science, 2018)
Segmental structure is common especially for a rotor in electrical motor. It is to reduce the cost of production, conveniently replace, and as a module where the sum of electromagnetic torque produced comes from each segmental stator add up together. Thus, in this paper will be focusing on the elementary analysis of a segmental stator for single phase 6Slot-12Pole and 3 phase 6Slot-15Pole Switched-Flux Permanent Magnet Machine (SFPMM) as the chosen design for analysis validation from coventional permanent magnet flux switching machine to a new segmental stator structure of SFPMM. It will be focusing on the initial design and to prove that it can be operate as a flux switching machine by implement a 2D Finite Element Analysis simulations such as a No-load analysis (flux linkage, cogging torque, back emf) and Load-analysis (average electromagnetic torque. Elementary result shows that the electromagnetic torque produce for both design are 10.6 Nm and 99.95 Nm and proved that it can produce high torque although it does not surpass the conventional SFPMM. A further research and optimization will be needed to obtain a higher torque compared to conventional SFPMM.